Evaluation of the role of intellectual capital in innovative economic growth in the framework of knowledge economy - H. Rahimli (Вісник аграрної науки Причорномор'я, 2021)
The article analyses the role of intellectual capital in innovative economic growth within the knowledge economy. To this end, the essence of social capital phenomena, one of the modern concepts of human capital and institutional economy, which are the main components of intellectual capital, is explained, as well as the impact of research and development activities on economic growth, one of the main indicators of scientific development